Factors affecting occupational safety and health behavior towards the incidence of work accidents in traditional fishermen in Bojo village, Barru district - Jamil, Sri Sisilawati; Thamrin, Yahya; Wahyu, Atjo; Saleh, Lalu Muhammad; Amir, Muhammad Yusran (Edelweiss Applied Science and Technology, 2026)
The fishing profession plays a very important economic role for coastal communities in Indonesia, but it also carries a high risk of occupational accidents due to environmental, technical, and human factors. This study aims to analyze the factors associated with occupational accidents among traditional fishermen in Bojo Village, Barru Regency, with a focus on Occupational Safety and Health (OSH) behavior and working conditions. The study used a quantitative design with a cross-sectional. The research sample consisted of 123 fishermen from all population with questionnaires. Data analysis used logistic regression to assess the influence of compliance of work accidents. The results of the analysis showed that the regression model had a good fit and was able to explain 64.7% of the variation in work accidents (R Square = 0.647). The variables of PPE compliance, working hours, length of service, climate and weather conditions, level of knowledge, trust, and availability of facilities and infrastructure were significantly related to work accidents (p<0.05), while age did not show a significant relationship (p>0.05). These findings confirm that behavioral, organizational, and environmental factors are the main determinants of safety for traditional fishermen.